Effects of Cyclic Chronic Heat Stress on the Expression of Nutrient Transporters in the Jejunum of Modern Broilers and Their Ancestor Wild Jungle Fowl - Abdelli, Nedra; Ramser, Alison; Greene, Elizabeth S.; Beer, Lesleigh; Tabler, Travis W.; Orlowski, Sara K.; Pérez, José Francisco; Solà-Oriol, David; Anthony, Nicholas B.; Dridi, Sami (Frontiers in Physiology, 2021)
The mechanisms associated between growth rate, gut integrity and heat stress (HS) responses are not known. The current study aimed to evaluate the effect of chronic HS on jejunal nutrient transport in slow- (ACRB from 1950), moderate- (95RAN from 1995), rapid-(modern broilers, MRB) growing birds, and their ancestor wild jungle fowl (JF). One-day male chicks (n=150/line) were placed by line in environmentally controlled chambers and kept under the same environmental conditions until d28. On d29, an 8-h daily cyclic HS (36ºC) was applied to half of the chambers, which lasts until d55, while keeping the rest under thermal neutral conditions (TN, 24°C). Jejunum tissues were collected for morphology assessment and molecular analysis of carbohydrate-, amino acid- and fatty acid- transporters. MRB exhibited the highest BW followed by 95RAN under both conditions. HS decreased FI in MRB and 95RAN, which results in lower BW compared to their TN counterparts, however no effect was observed in ACRB and JF. MRB showed greater villus height to crypt depth ratio under both environmental conditions. Molecular analyses showed that GLUT2, 5, 10, and 11 were upregulated in MRB compared to some of the other populations under TN conditions. HS down regulated GLUT2, 10, 11, and 12 in MRB while it increased the expression of GLUT1, 5, 10, and 11 in JF. GLUT2 protein expression was higher in JF compared to ACRB and MRB under TN conditions. It also showed an increase in ACRB but no effect on 95RAN and MRB under HS conditions. ACRB exhibited greater expression of EAAT3 gene as compared to the rest of populations maintained under TN conditions. HS exposure did not alter the gene expression of amino acid transporters in MRB. Gene expression of CD36 and FABP2 was up-regulated in HS JF birds. Protein expression of CD36 was down-regulated in HS JF while no effect was observed in ACRB, 95RAN and MRB. Taken together, these data are the first to show the effect of HS on jejunal expression of nutrient transporters in three broiler populations known to represent 70 years of genetic progress in the poultry industry